Hubungan Pengetahuan Etika Profesi Terhadap Kepatuhan Hukum Kesehatan pada Alumni D3 Kebidanan STIKes Pondok Pesantren Assanadiyah yang Bekerja di Instansi Kesehatan Tahun 2025: Penelitian - Junawalia Mayang Sari; Mariyam; Umi Solekah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Professional ethics and health law are important aspects in midwifery practice. This study aims to analyze the relationship between professional ethics knowledge and health law compliance among D3 Midwifery alumni from STIKes Pondok Pesantren Assanadiyah Palembang who work in health institutions. The study used a quantitative approach with a cross-sectional design and involved 50 respondents selected through purposive sampling. The research instrument was a questionnaire on professional ethics knowledge (midwife-patient rights and obligations, patient confidentiality, and informed consent) and health law compliance. Data analysis was performed univariately and bivariately using the Chi-square test. The results showed that most respondents had good knowledge of rights and obligations (66%), patient confidentiality (64%), and informed consent (64%), with a high level of health law compliance (68%). Bivariate analysis showed a significant relationship between knowledge of rights and obligations (p=0.001; OR=10.267), patient confidentiality (p=0.000; OR=14.000), and informed consent (p=0.000; OR=9.000) and health law compliance. This study emphasizes the importance of increasing understanding of professional ethics and health law to support professional and responsible midwifery practice.